The Strategi Pengembangan Wisata Taman Gandrung Terakota Kabupaten Banyuwangi - Kurniawati, Risa Amalia; Shaherani, Natasya; Rahmawati, Dewi; Astina, I Komang (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2022)
This study aims to analyze the strengths, weaknesses, opportunities, and threats in the development of the Gandrung Terracotta Park tourism object in the Banyuwangi Regency. This research is qualitative research with quantitative methods using IFAS, EFAS, and SWOT quadrant analysis methods. The results showed that the opportunity factor for developing terracotta park tourism had the greatest weight compared to other external factors. In general, the amount of weight on external factors ranges from 0.23 to 0.29. The results of the calculation of the total weighted value of external factors obtained the results that the total value is 2.16. The garden of gandrung terracotta is in quadrant 1 where this condition is very beneficial for the owner because it has strengths and opportunities if you can use it well. The strategy that must be applied in this condition is to support the growth policy (Growth Oriental Strategy). Although there are several weaknesses and threats that are quite large, these attractions can take advantage of opportunities and strengths so that they can make these attractions develop. Keywords: Terracotta Gandrung Park, Culture Tour, SWOT Analysis